Reliability and validity evaluation of the Chinese version of the gender misconceptions of men in nursing (GEMINI) scale among nursing students - Huameng Xu; Chunguang Liang; Jie Kong; Qing Chen; Ying Zhao; Fan Zhang (BMC, 2024)
Abstract Background Misconceptions about male nurses not only exacerbate the gender imbalance in the nursing profession but also negatively impact male nurses embarking on their careers. Currently, no tool exists to measure the gender biases toward males in nursing among nursing students in China. Consequently, the primary objective of this study is to assess the validity and reliability of the Chinese translation of the Gender Misconceptions of Men in Nursing (GEMINI) scale among nursing students. Methods This cross-sectional study involved 1,102 nursing students from China who participated online. We utilized the Brislin translation technique with a forward-backward approach. To determine the factor structure within the Men in Nursing Gender Misconceptions Scale's Chinese version, both exploratory (EFA) and confirmatory factor analysis (CFA) were applied. The scale's internal consistency was measured through the Cronbach's alpha coefficient, corrected item-total correlation, and a retest reliability assessment. Results The scale showed a content validity index of 0.938 and a retest reliability of 0.844. EFA indicated a two-factor structure for the translated instrument. CFA revealed a chi-square/degree of freedom of 3.837, an incremental fit index (IFI) of 0.952, a goodness-of-fit index (GFI) of 0.910, a comparative fit index (CFI) of 0.952, and an RMSEA of 0.073, all of which were within acceptable limits. The scale's Cronbach's α was 0.953, and the corrected item-total correlations ranged between 0.539 and 0.838. Gender-based misconceptions about men in nursing among students appeared to be influenced by their gender and whether they considered a nursing program as their first choice when applying for a major. Misconceptions about male nurses are greater among men and those who do not consider nursing programs as their first choice when applying for a major. Conclusions The Chinese adaptation of the GEMINI scale showcased high reliability and validity. It stands as a potential instrument to gauge gender misconceptions concerning male nurses among Chinese nursing students.